The Influence of Product Quality and Physical Environment on Repurchase Interest Through Customer Satisfaction of Warteg Kharisma Bahari in Bekasi City - Zaky Achmad; Dr. Ismail Razak, M.Si. (Krisnadwipayana International Journal of Management Studies, 2023)
The purpose of this study is to determine and analyze the effect of product quality and physical environment on repurchasing interest through customer satisfaction on Warteg Kharisma Bahari in Bekasi City. This research is quantitative research using a descriptive correlation design with a cross sectional approach. The population in this study are the customers of Warteg Kharisma Bahari in Bekasi City whose number is unknown. The sample in this study was 100 people who were taken by non-probability sampling technique with incidental sampling technique. The data collection technique is by using a questionnaire. The analytical method used are descriptive analysis method and path analysis method. The results showed that the product quality variable and the physical environment variable simultaneously had a positive and significant effect on customer satisfaction. Product quality and physical environment variables have a negative and not significant effect on repurchasing interest. The variable of customer satisfaction has a positive and significant effect on repurchasing interest. Furthermore, the customer satisfaction variable is able to mediate between the product quality and physical environment variables on the repurchasing interest variable.